2019
DOI: 10.3389/fmicb.2019.02067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Targets for Coevolutionary Interactions Between Pacific Oyster Larvae and Their Sympatric Vibrios

Abstract: Bacteria of the Vibrio genus are the most predominant infectious agents threatening marine wildlife and aquaculture. Due to the large genetic diversity of these pathogens, the molecular determinants of Vibrio virulence are only poorly understood. Furthermore, studies tend to ignore co-evolutionary interactions between different host populations and their locally encountered Vibrio communities. Here, we explore the molecular targets of such co-evolutionary interactions by analyzing the genomes of nine Vibrio st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
(109 reference statements)
0
9
0
Order By: Relevance
“…For example, the bacterium Aeromonas veronii, after several passages through its zebrafish host, evolved and selected for a more host-adapted derivative that was more effective at tissue migration (19). Similarly, analyses of Vibrio splendidus strains have provided evidence for allelic selection in two core genome genes that determine the bacterium's interaction with oyster larvae (32). Thus, one can envision two possible reasons for the dispersed distribution of dominant behavior seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the bacterium Aeromonas veronii, after several passages through its zebrafish host, evolved and selected for a more host-adapted derivative that was more effective at tissue migration (19). Similarly, analyses of Vibrio splendidus strains have provided evidence for allelic selection in two core genome genes that determine the bacterium's interaction with oyster larvae (32). Thus, one can envision two possible reasons for the dispersed distribution of dominant behavior seen in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…And while we have successfully identified the molecular targets of the specific host x pathogen interactions on the Vibrio pathogen side (Wegner et al, 2019), we lack an understanding of the genomic architecture of resistance of the oyster host. One of the identified Vibrio genes, OG1907 (Wegner et al, 2019) contained a Glycosyl Hydrolase 3 domain (PF00933) that could potentially be involved in modification of the complex sugar composition of the LPS (Simpson and Trent, 2019), thereby establishing a potential link to the outlier loci found here if they target galactose in LPS of Vibrio. The importance of galactose binding by C-type lectins was also reflected in the transcriptomes, where a galactose binding domain was annotated in eight differentially expressed genes.…”
Section: Discussionmentioning
confidence: 99%
“…By exploiting the specific natural history of these oyster populations, it was already shown that oysters from both invasions locally adapted to their sympatric communities of pathogenic Vibrio bacteria (Wendling and Wegner, 2015). Genomic comparisons of these Vibrio communities revealed that only few molecular targets were involved on the pathogen side (Wegner et al, 2019). While adaptive genetic divergence of oyster hosts remains unknown, these results may suggest that processes involved in the immune defense might show matching patterns of adaptive divergence.…”
Section: Introductionmentioning
confidence: 91%
“…Flavobacterium) [6]. Some readily culturable members of the oyster microbiome, such as strains of the Vibrio genus, have been closely studied to profile their abundance [7], pathogenic potential [8], evolution and diversity [9], and inhibition of growth by probiotics [10,11]. Other well known, cultured microbes from oysters include the protozoan pathogen Perkinsus marinus, a causative agent of Dermo disease, which is one of the major diseases of adult eastern oysters [12].…”
Section: Introductionmentioning
confidence: 99%